Different types of membrane materials for oil-water separation: Status and challenges - Xin, Yanping; Qi, Bo; Wu, Xiao; Yang, Chao; Li, Bingfan (Colloid and interface science communications, 2024)
Oily wastewater can have a great impact on human health and the surrounding environment. The current methods for treating oily wastewater mainly included physical methods, chemical methods, membrane separation technology and other mechanical methods. Compared with other methods, membrane separation technology had the advantages of high separation efficiency, low cost, simple operation, energy saving and environmental protection in separating general oil-water emulsions, thus having a wide application prospect. In order to understand the application of membrane materials in oil-water separation, such as improving the structure, mechanical strength and structural stability of membrane materials in aqueous solutions, this paper discussed the separation mechanism of oily wastewater by different membrane materials (inorganic membranes, organic membranes and emerging membrane). The latest research progress of various types of membranes and the strategies and performance of membrane modification were introduced and analyzed. In the end, the future development direction of membrane separation technology was summarized. The future research will be focused on reducing the cost of membrane preparation, reducing the pollution to the environment, using natural membrane materials, developing molecular-level methods for membrane anticontamination, exploring more stable surface modification methods, and quantitatively analyzing the influence of surface structure on membrane surface-water-pollutant interactions at molecular level. [Display omitted] •Summarized the mechanism and latest progress of different membrane materials for separating oily wastewater.•The performance difference of different types of membranes in separating oil-water emulsion was compared.•It is pointed out that the focus of future research on oil-water separation membranes.